A Review of Artificial Intelligence in the Internet of Things - González García, Cristian; Núñez-Valdez, Edward; García-Díaz, Vicente; Pelayo García-Bustelo, B. Cristina; Cueva-Lovelle, Juan Manuel (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2022)
Humankind has the ability of learning new things automatically due to the capacities with which we were born. We simply need to have experiences, read, study… live. For these processes, we are capable of acquiring new abilities or modifying those we already have. Another ability we possess is the faculty of thinking, imagine, create our own ideas, and dream. Nevertheless, what occurs when we extrapolate this to machines? Machines can learn. We can teach them. In the last years, considerable advances have been done and we have seen cars that can recognise pedestrians or other cars, systems that distinguish animals, and even, how some artificial intelligences have been able to dream, paint, and compose music by themselves. Despite this, the doubt is the following: Can machines think? Or, in other words, could a machine which is talking to a person and is situated in another room make them believe they are talking with another human? This is a doubt that has been present since Alan Mathison Turing contemplated it and it has not been resolved yet. In this article, we will show the beginnings of what is known as Artificial Intelligence and some branches of it such as Machine Learning, Computer Vision, Fuzzy Logic, and Natural Language Processing. We will talk about each of them, their concepts, how they work, and the related work on the Internet of Things fields.
Keywords: computer vision; artificial intelligence; machine learning; learning systems; fuzzy logic; natural language processing; IJIMAI